Alternating-current conductivity and dielectric relaxation of bulk iodoargentate. (May 2015) - Duan, Hai-Bao; Yu, Shan-Shan; Zhou, Hong
Graphical abstract: The electric modulus shows single dielectric relaxation process in the measured frequency range. Highlights: The conduction mechanism is described by quantum mechanical tunneling model. The applications of dielectric modulus give a simple method for evaluating the activation energy of the dielectric relaxation. The [Ag2 I4 ] 2− 1-D chain and [Cu(en)2 ] 2+ cation column form the layered stacks by hydrogen bond interactions. Abstract: An inorganic-organic hybrid compound Cu(en)2 Ag2 I4 (en = ethylenediamine) (1 ) was synthesized and single crystal structurally characterized. Along the [001] direction, the inorganic parts form an infinite 1-D chain and [Cu(en)2 ] 2+ cations are separated by inorganic chain. The electrical conductivity and dielectric properties of1 have been investigated over wide ranges of frequency. The alternating-current conductivities have been fitted to the Almond–West type power law expression with use of a single value of S. It is found that S values for1 are nearly temperature-independent, which indicates that the conduction mechanism could be quantum mechanical tunneling (QMT) model. The dielectric loss and electric modulus show single dielectric relaxation process. The activation energy obtained from temperature-dependent electric modulus compare with the calculated from the dc conductivity plots.